A percepção da enfermeira sobre o processo decisório e os cuidados de final de vida em Unidade de Terapia Intensiva Pediátrica - Nilson, Cristine (2017)
CONTEXT: For more than 30 years, we have observed a growing concern about the way of dying in Pediatric Intensive Care Units (PICUs), which is expressed through a growing number of studies and publications on this topic, focusing on the quality of care that is provided at the end of life for those patients who no longer benefit from any therapeutic support, as the possibilities of healing have been exhausted. For intensive therapy professionals, who usually associate death with failure, the first great challenge may be to let go of the therapeutic resources that are no longer appropriate for saving a life, but are capable of generating and prolonging the suffering of the patient and his or her family if they are poorly utilized. Terms such as therapeutic obstinacy and futile care need to be understood and, above all, they need to give rise to a conduct of resignation in the face of death. We have verified a paradigm shift from a model of healing to one of comfort and, consequently, the emergence of a new field of expertise for the multidisciplinary team: palliative care. The model of the decision-making process related to end-of-life care that is internationally advocated presupposes the participation of the multidisciplinary team, but what we still observe in our environment is an incipient participation of the nurses, who could play a decisive role in the definitions and in the dialogue regarding desires that are expressed by the patient’s family, considering their proximity to and involvement with the family. This study proposes some types of intervention and the organization of support systems which could be incorporated to improve the process of care at the end of life, among them: systematically including the topics of Therapeutic Support Limitation (TSL) and palliative care in the continuing education program for the multidisciplinary team of the PICU; monitoring of the nursing staff by psychology services, and paying special attention to the signs of moral distress and preparation for mourning, given the proximity and identification of these professionals with the patients and their families in the situation of suffering. OBJECTIVE: This study aims to describe the facilities and barriers that occur in our environment as related to the participation of nurses in the decision-making process about end-of-life care, as well as the perception of these professionals regarding the care provided to the patient and his or her family. METHOD: Individual, semi-structured interviews were conducted with nurses who participated in the TSL decision-making process, and who provided care to the patient and his or her family in the final hours of life of 16 children who died in the PICU of the Hospital de Clínicas (Clinical Hospital) of Porto Alegre ( HCPA) and the Hospital of the Pontifical Catholic University of Rio Grande do Sul (HSL-PUCRS). CONCLUSIONS: Situations in which patients have reserved prognoses are increasingly frequent in PICUs and require those who care for these patients to be proficient, not only in saving lives, but also in providing palliative care. The participation of a nurse in the decision-making process about TSL is incipient, it is consensual in character in relation to medical definitions, and the main barriers to participation lie in the lack of expertise regarding the subject. A nurse plays an important role in the emotional support of a terminally ill patient and his or her family, as well as mediating the communication between the multidisciplinary team and the family. The analysis of nurses' perceptions of end-of-life care suggests the need to establish an emotional support plan for these professionals who experience death and suffering in the routine of their work, thus promoting better care for terminally ill patients In PICUs. The decision-making process about end-of-life care involving TSL, and whether or not treatment is withdrawn, is a subject that still needs to be discussed and studied.